2023
DOI: 10.25130/tjps.v21i1.949
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical constituents and nutrient evaluation of date palm (Phoenix dactylifera, L.) pollen grains

Abstract: The pollen of date palm -DPP (Phoenix dactylifera L. variety El- Ghannmi Ahmar.) has been analyzed for the main phytochemical composition , nutrient and mineral composition. The phytochemical screening of chemical constituents of the plant showed that the DPP grains contains phytosterols, flavonoids, alkaloids, protein, carbohydrates, glycosides, phenolic compounds, tannins, terpenoids, saponins, coumarins, lignin, oil and fats, with absent of quinones. The quantitative contents of  alkaloids, tannin, phenolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several studies have examined the carbohydrate content in DPP across different varieties and regions ( Table 4 ). The highest percentage was observed in Moroccan DPP at 26.51% [ 11 ], followed by the Ghannamy Ahmar variety grown in Iraq, which reached a percentage of 26.25% [ 37 ]. Another study reported that Iraqi Khikri and Samsami DPP contain 16.27% and 22.78% of carbohydrates, respectively [ 39 ].…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined the carbohydrate content in DPP across different varieties and regions ( Table 4 ). The highest percentage was observed in Moroccan DPP at 26.51% [ 11 ], followed by the Ghannamy Ahmar variety grown in Iraq, which reached a percentage of 26.25% [ 37 ]. Another study reported that Iraqi Khikri and Samsami DPP contain 16.27% and 22.78% of carbohydrates, respectively [ 39 ].…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%
“…Moreover, DPP from the El-Ghannmi Ahmar cultivated in Iraq has demonstrated even higher mineral contents compared to Egyptian DPP. Specifically, the Iraqi DPP revealed elevated levels of potassium (7350 mg/100 g), magnesium (1960 mg/100 g), calcium (1080 mg/100 g), iron (8500 mg/100 g), and copper (365 mg/100 g), in comparison to Egyptian DPP [ 37 ] ( Table 5 ).…”
Section: Exploring Mechanisms: How Date Palm Pollen Composition Influ...mentioning
confidence: 99%
See 1 more Smart Citation